Specific Methodological Approach for Establishing and Verifying Cause in Forensic Examination - F. G. Aminev; S. A. Zamyatin (Теория и практика судебной экспертизы)
The task of establishing the cause of certain facts, events, or processes is one of the most common tasks that courts systematically assign to experts. The article presents a methodological approach for justifying the cause during the preparation of a written opinion within the framework of forensic examination. This approach allows to identify the cause of the investigated event among various factors and can be useful in the context of forensic investigation both to justify conclusions about the cause and to verify the completeness and reliability of the conducted investigation as an express analysis.